3‐T MRI of protothecosis encephalic lesions in a Scottish shepherd dog. Issue 3 (23rd September 2020) - Cocchetto, Aurora; Briola, Chiara; Furlanello, Tommaso; Danesi, Patrizia; Cirla, Alessandro; Menchetti, Marika
Abstract : A four‐year‐old Scottish Shepherd dog was referred for acute onset of disorientation, blindness and chronic diarrhoea. The neurological examination was consistent with a multifocal neurolocalisation involving the prosencephalon and the brainstem. The ophthalmological exam showed bilateral chorioretinitis with retinal detachment. The brain MRI showed periventricular and left caudate nucleus lesions, increased thickness of the left III, IV, VI and opthalmic branch of V cranial nerves and bilateral multifocal lesions in the temporal and masseter muscles. Cerebrospinal fluid examination showed mild mixed pleocytosis. Faecal and urine cultures were positive for Prototheca zopfii genotype 2. Despite starting itraconazole therapy, the dog's conditions deteriorated and the owner elected euthanasia. Protothecosis should be suspected in young dogs with multifocal neurological signs, blindness and chronic diarrhoea. MRI study of the central nervous system (CNS), together with blood exam, cytology and cultures, is a useful tool to evaluate the CNS in disseminated form of Prototheca infection.